1952
DOI: 10.1017/s0041977x00084251
|View full text |Cite
|
Sign up to set email alerts
|

The Main Features of Cambodian Pronunciation

Abstract: The pronunciation here described is that of Mr. Keng Vannsak, a young Cambodian born at Kompong Chhnang.The words quoted in illustration of the text are shown both in Cambodian script and in a simplified phonetic transcription based on that of the International Phonetic Association. Where it has been considered useful, a more detailed transcription in general phonetic terms has been given in square brackets. All examples have been checked with a second Cambodian, Mr. Keo Mongkry, and where his usage differs fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
2

Year Published

1965
1965
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(48 citation statements)
references
References 1 publication
0
46
0
2
Order By: Relevance
“…Conversely, Thongkum (1988) reports that breathiness is associated with a lowering of the first formant in Chong, though she does not observe this difference in the related languages Nyah Kur and Kui. Based on observations of other scholars (Henderson 1952, Gregerson 1976), Thongkum suggests that the lowering of the first formant during breathy phonation in Chong might be attributed to larynx lowering; this explanation would fit in with the suggestion of Kirk et al (1993) that the opposite effect, the raising of the first formant during creaky phonation, is an acoustic correlate of larynx raising. Samely (1991) also found that breathy vowels have lower first and second formant values than modal vowels in Kedang, though it should be pointed out that breathy vowels in this language are associated with increased pharyngeal width which could contribute to the observed formant differences.…”
Section: Formant Frequenciesmentioning
confidence: 57%
“…Conversely, Thongkum (1988) reports that breathiness is associated with a lowering of the first formant in Chong, though she does not observe this difference in the related languages Nyah Kur and Kui. Based on observations of other scholars (Henderson 1952, Gregerson 1976), Thongkum suggests that the lowering of the first formant during breathy phonation in Chong might be attributed to larynx lowering; this explanation would fit in with the suggestion of Kirk et al (1993) that the opposite effect, the raising of the first formant during creaky phonation, is an acoustic correlate of larynx raising. Samely (1991) also found that breathy vowels have lower first and second formant values than modal vowels in Kedang, though it should be pointed out that breathy vowels in this language are associated with increased pharyngeal width which could contribute to the observed formant differences.…”
Section: Formant Frequenciesmentioning
confidence: 57%
“…This study investigates the phonetics of register in the dialect of Chong spoken in the Takhian Thong community. The term register is used in the Southeast Asian linguistic literature with reference to a collection of contrastive suprasegmental properties like phonation type, pitch, vowel quality, intensity and vowel duration (Henderson 1952(Henderson , 1985. A register language is distinct from a tone language because contrastive phonation type typifies the former while the contrastive pitch typifies the latter.…”
Section: Introductionmentioning
confidence: 99%
“…The concept of voice type register was initially applied to the vowel system of modern Mon (Jenner 1974), although illustrations of register were first published by Henderson (1952), concerning Khmer, and then by Shorto (1962: introduction), concerning Mon.…”
Section: Registrogenesis By Initialsmentioning
confidence: 99%
“…Attempts at synthesis concerning these crucial issues of registrogenesis in the languages of Southeast Asia have been published by several scholars, among them Gregerson (1976), Huffman (1976), Ferlus (1979: this study needs to be corrected and updated; the author advises the reader to overlook paragraphs 14-17), Theraphan (1988). The founder article, however, is indisputably that written by Henderson (1952).…”
Section: Registrogenesis By Initialsmentioning
confidence: 99%